2020
DOI: 10.1051/0004-6361/201936765
|View full text |Cite
|
Sign up to set email alerts
|

Rise and fall of the high-energy afterglow emission of GRB 180720B

Abstract: The Gamma Ray Burst (GRB) 180720B is one of the brightest events detected by the Fermi satellite and the first GRB detected by the H.E.S.S. telescope above 100 GeV. We analyse the Fermi (GBM and LAT) and Swift (XRT and BAT) data and describe the evolution of the burst spectral energy distribution in the 0.5 keV-10 GeV energy range over the first 500 seconds of emission. We reveal a smooth transition from the prompt phase, dominated by synchrotron emission in a moderately fast cooling regime, to the afterglow p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 73 publications
4
22
0
Order By: Relevance
“…A prototypical example, GRB 180720B at z = 0.65 (Fig. 6 top left panel) observed by Fermi/GBM, revealed [99] a steep electron energy distribution (inferred from the slope of the high energy power law spectrum) and a relatively small comoving frame magnetic field, which challenge the acceleration mechanisms, the common understanding of the jet composition, and the standard electron-synchrotron scenario [50].…”
Section: The Nature Of the Prompt Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prototypical example, GRB 180720B at z = 0.65 (Fig. 6 top left panel) observed by Fermi/GBM, revealed [99] a steep electron energy distribution (inferred from the slope of the high energy power law spectrum) and a relatively small comoving frame magnetic field, which challenge the acceleration mechanisms, the common understanding of the jet composition, and the standard electron-synchrotron scenario [50].…”
Section: The Nature Of the Prompt Emissionmentioning
confidence: 99%
“…For instance, at z ∼2, corresponding to the peak of the THESEUS-detected population, the break energy will be constrained with an accuracy of 20% compared to >50% of Fermi (compare solid and dashed black lines Fig. 6 Simulated prompt emission spectrum of GRB 180720B [99] as observable by Fermi/GBM (top left panel) and by THESEUS/SXI+XGIS (bottom left panel). The assumed spectral model is a double break power-law [95] with parameters from [99].…”
Section: Accuracy Of Spectral Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-energy part of the observed spectrum, however, is harder than the predicted value, having α ∼−1. A major ease to this situation came with the discovery that many GRB spectra have a spectral break in the low-energy part [79,80]: in this case, the spectral regime α = −0.67 is visible inside the energy rage of the soft/hard X-ray instruments, and the spectral break (identified between 1-100 keV [79][80][81][82][83][84]) connects the segment α 1 = −0.67 with the segment α 2 = −1.5. In this configuration (sometimes named marginally fast cooling [85]), the break is identified with the cooling break frequency, and the radiation efficiency is still large and does not affect the estimates on the jet energetics.…”
Section: Prompt Emissionmentioning
confidence: 99%
“…In addition, the authors did not attempt to fit this theoretical model to the data, which might introduce instrumental biases in the comparison with the Band fit results. Direct fits of the synchrotron emission model to GRB prompt spectra have been performed by Zhang et al (2016) and Burgess (2019), who showed that the line-of-death and spectralsharpness issues are likely artefacts due to the use of the Band function (see also Ronchi et al 2020). Fitting the spectra with simpler versions of the synchrotron emission model or with empirical functions featuring a low-energy spectral break, especially on a broad energy range extending down to the X-ray and/or optical domain, appears able to reconcile the observations with the synchrotron theory as well, showing the expected transition from fast to slow cooling (Oganesyan et al 2017(Oganesyan et al , 2018(Oganesyan et al , 2019Ravasio et al 2018Ravasio et al , 2019.…”
Section: Introductionmentioning
confidence: 99%